(untitled) (Eurasian Scientific Herald, 2022)
According to experts, the annual economic damage from the state of emergency restrains the socio-economic development ofboth the regions and the whole country. Currently, the negative processes taking place in the economy require a transition from gratuitous financing of expenses for the elimination of the consequences of emergency situations at the expense of the state budget to oblivion time-based planning and insurance of these expenses. The use of emergency insurance reduces the burden on all other sources of emergency response.